Double emulsion followed by complex coacervation as a promising method for protection of black raspberry anthocyanins. (April 2018) - Shaddel, Rezvan; Hesari, Javad; Azadmard-Damirchi, Sodeif; Hamishehkar, Hamed; Fathi-Achachlouei, Bahram; Huang, Qingrong
Abstract: Black raspberry is an important source of anthocyanins, which are profoundly colored materials, known for their antioxidant activity. However, their usage in food industry is restricted mainly because of their low stability, especially under harsh conditions. To overcome the instability of these water soluble compounds, a double emulsion technique prior to complex coacervation was applied by gelatin and gum Arabic as wall materials after preparing the water-in-oil emulsion. The coacervation process was investigated as a function of gelatin, gum Arabic and the core material concentrations at ratios of 1:1:0.5, 1:1:0.75 and 1:1:1, the concentration of polymer solutions (2.5, 5.0 and 7.5%, w/v) as well as pH (3.5, 4.0, 4.5 and 5.0). The pH 4.0 was selected as optimum pH for gelatin/gum Arabic coacervation. The morphology, particle size, moisture, solubility, hygroscopicity, zeta potential, loading capacity, color parameters ( L*, a*, b*, C, H◦ and TCD ), stability, Fourier transform infrared spectroscopy (FTIR), thermal behavior and X-ray diffraction (XRD) pattern were obtained. The microcapsules presented the spherical shape and relatively smooth surface by the average sizes ranging from 45.25 ± 0.97 to 109.49 ± 4.77 μm. The loading capacity was high (23.27 ± 0.42 to 41.72 ± 0.30%). There was a good correlation between zeta potential values and FTIR spectra, indicating the chemical cross-linking reaction. DSC thermograms confirm the thermostability of microcapsules. XRD pattern was in line with DSC results, indicating the amorphous structure of unencapsulated core anthocyanins. Furthermore, the HPLC and color analysis results demonstrating the high retention of microencapsulated anthocyanins (up to 36%) as comparing the control sample after 2 months of storage at 37 ± 2 °C, suggesting that the method chosen to protect the anthocyanins was effective. Graphical abstract: Image 1 Highlights: Microencapsulation of black raspberry extract by complex coacervation. Viability of microencapsulation of hydrophilic compounds was proved. The coacervate formulations were effective to encapsulate anthocyanins by high loading capacity. High protection of encapsulated anthocyanins as comparing the free unencapsulated form was obtained. A potential natural colorant for food and nutraceutical uses was introduced.